Analysing Social Policy: A Governmental Approach (Edward Elgar, 2006)
This book brings together leading international researchers to discuss governmental approaches to analysing social policies. Analysing Social Policy expands the scope of social policy analysis using the insights from post-Foucauldian scholarship on the art of governing in liberal democracies. One of the main conclusions reached is that policy researchers need to pay much greater attention to the minutiae of policy reform, and to the discursive and material ways in which power operates in policy change. The chapters comprising this book are purposefully written in a clear, accessible and reflective manner, with each of the contributions empirically grounded, drawing on social policy problems and practices in many countries, ranging from North America to Europe to Australasia. The editors address key concerns of both policy analysts as well as academic researchers attempting to locate appropriate theoretical frameworks to make sense of welfare state restructuring in the 21st century. This book will appeal to researchers and research students in political science, social policy, social work and sociology through its demonstration of how to apply contemporary social theory to research problems. It will also be of interest to policy scholars around the world who are involved in analysing the intersections of power, politics and policy.